Functional connectivity in resting-state fMRI: is linear correlation sufficient? - Hlinka, Jaroslav; Palus, Milan; Vejmelka, Martin; Mantini, Dante; Corbetta, Maurizio (NeuroImage, 2011)
Functional connectivity (FC) analysis is a prominent approach to analyzing fMRI data, especially acquired under the resting state condition. The commonly used linear correlation FC measure bears an implicit assumption of Gaussianity of the dependence structure. If only the marginals, but not all the bivariate distributions are Gaussian, linear correlation consistently underestimates the strength of the dependence. To assess the suitability of linear correlation and the general potential of nonlinear FC measures, we present a framework for testing and estimating the deviation from Gaussianity by means of comparing mutual information in the data and its Gaussianized counterpart. We apply this method to 24 sessions of human resting state fMRI. For each session, matrix of connectivities between 90 anatomical parcel time series is computed using mutual information and compared to results from its multivariate Gaussian surrogate that conserves the correlations but cancels any nonlinearity. While the group-level tests confirmed non-Gaussianity in the FC, the quantitative assessment revealed that the portion of mutual information neglected by linear correlation is relatively minor-on average only about 5% of the mutual information already captured by the linear correlation. The marginality of the non-Gaussianity was confirmed in comparisons using clustering of the parcels-the disagreement between clustering obtained from mutual information and linear correlation was attributable to random error. We conclude that for this type of data, practical relevance of nonlinear methods trying to improve over linear correlation might be limited by the fact that the data are indeed almost Gaussian.
Keywords: algoritmy; Algorithms; Fourierova analýza; lineární modely; mužské pohlaví; Normal Distribution; Adult; mladý dospělý; Cluster Analysis; magnetická rezonanční tomografie; normální rozdělení; Linear Models; Magnetic Resonance Imaging; kyslík; Neural Pathways; Young Adult; ženské pohlaví; Humans; Rest; Software; odpočinek; Fourier Analysis; nervové dráhy; software; dospělí; Oxygen; Female; shluková analýza; lidé; Male